2022
DOI: 10.3390/plants11040573
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Fingerprinting and Molecular Characterization of the Rock Samphire Germplasm Collection from the Balkan Botanic Garden of Kroussia, Northern Greece

Abstract: The traditionally edible aerial parts of rock samphire (Crithmum maritimum L.) could be a valuable functional food or feed ingredient due to their high antioxidant capacity, ascorbic acid content, and rich content in secondary metabolites such as phenolics and flavonoids. The first objective of this study was to evaluate eighteen genotypes derived from different regions of Greece regarding the phytochemical contents of their soluble extracts in total phenolics, total flavonoids, and individual polyphenols as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Meot Duros and Magné [ 37 ] reported that sea fennel is one of the species with the highest chlorogenic acid content within the Apiaceae family. The presence of this compound in the highest concentration in sea fennel was also reported in our previous studies [ 8 , 9 ] and by other authors [ 3 , 4 , 5 , 10 , 11 , 12 ]. Among other compounds, two isomers of chlorogenic acid were found in high concentrations: cryptochlorogenic acid (4- O -caffeoylquinic acid) and neochlorogenic acid (5- O -caffeoylquinic acid).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Meot Duros and Magné [ 37 ] reported that sea fennel is one of the species with the highest chlorogenic acid content within the Apiaceae family. The presence of this compound in the highest concentration in sea fennel was also reported in our previous studies [ 8 , 9 ] and by other authors [ 3 , 4 , 5 , 10 , 11 , 12 ]. Among other compounds, two isomers of chlorogenic acid were found in high concentrations: cryptochlorogenic acid (4- O -caffeoylquinic acid) and neochlorogenic acid (5- O -caffeoylquinic acid).…”
Section: Resultssupporting
confidence: 87%
“…Among the constituents that sea fennel contains, phenolic compounds are the most widely investigated because they are secondary plant metabolites with a wide range of structures and positive biological functions. Numerous previous studies also confirmed the presence of valuable phytochemicals (from Table 2 ) in sea fennel samples as the main bioactive compounds [ 4 , 5 , 7 , 8 , 9 , 11 , 12 , 22 , 36 ].…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations